Characterisation of the transcriptional potential of intergenic CCG-repeats - Cozens, Jacob (Cranfield University, 2011)
CCG repeats have been found to have a non random distribution throughout the human genome. Previous analysis of ChIP-seq data from 800 intergenic CCG-repeats shows that they are associated with RNA polymerase II and several histone modifications that characterise transcription initiation including H3K4me3. RNA polymerase II, H3K4me3 and nucleosome distribution profiles have been analysed at these repeat regions using computer programming techniques. These profiles have in part been found to be similar to those observed at transcription start sites and so this raises the potential for CCG repeats to be implicated as alternative sites for transcription initiation.
Keywords: human genome; RNA polymerase; nucleosome distribution profiles; CCG repeats; ChIP-seq data